Modeling of useful operating life of radioelectronics - Nevlyudova, V. V. (Technology and design in electronic equipment, 2014)
The author considers the possibility of using the laws of nonequilibrium thermodynamics to determine the relationship between controlled parameters of radioelectronics and the displayed environment, as well as the construction of a deterministic model of the processes of manufacturing defects development. This possibility is based on the observed patterns of change in the amount of content area, in accordance with the principles of behaviour of the thermodynamic parameters characterizing the state of the real environment (entropy, the quantity of heat, etc.). The equation for the evolution of the technical state of radioelectronics is based on the deterministic kinetic model of the processes occurring in the multi-component environment, and on the observation model, which takes into account the errors caused by external influences instability and uncertainty.